A controllable deflection routing and wavelength assignment algorithm in OBS networks - Khumalo, Philani; Nleya, Bakhe; Mutsvangwa, Andrew (Journal of optics (New Delhi), 2019)
Heterogeneous IoT-enabled networks generally accommodate both jitter-tolerant traffic and jitter-intolerant traffic. Optical burst-switched backbone networks are handling the resultant volumes of such traffic by transmitting it in huge-size chunks called bursts. Because of the lack or limited buffering capabilities within the core network, contentions as well as congestion may frequently occur, thus affecting overall supportable quality of service (QoS). Both contention and congestion will be characterized by frequent burst losses, especially when traffic levels surge. The congestion is normally resolved by way of deflecting contending bursts to other less congested paths even though this may lead to differential delays incurred by bursts as they traverse the network. This will contribute to undesirable jitter that may ultimately compromise overall QoS. Noting that jitter is mostly caused by deflection routing which itself is a result of poor wavelength and routing assigning, in this paper we propose a controllable deflection routing scheme that allows the deflection of bursts to alternate paths only after controller buffer preset thresholds are surpassed. In this way, bursts intended for a common destination are always most likely to be routed on the same or least-cost path end-to-end. We describe the scheme and compare its performance to other existing approaches. Both analytical and simulation results overall show that the proposed scheme does lower both congestion and jitter, thus also improving throughput as well as avoiding congestion on deflection paths.